Your life is now - Mellencamp, John; Sony Music Entertainment (New York : Sony Music Entertainment, 1998)
Contains songs of heartland rock genre.
Violin version (4:00) -- Guitar version (3:57) -- Violin version callout hook #1 (:10) -- Violin version callout hook #2 (:05) -- Guitar version callout hook #1 (:10) -- Guitar version callout hook #2 (:05).
Koleksi Khas Wiramanja.
Title from container.
Keywords: Songs, English